Effects of Additives in Shoot Multiplication and Genetic Validation in Swertica chirayita Revealed through RAPD Analysis - Sharma, Vikas; Kamal, Barkha; Srivastava, Nidhi; Dobriyal, Anoop Kumar; Jadon, Vikash Singh (Plant Tissue Culture and Biotechnology, 2013)
Enhanced in vitro caulogenesis has been tested in Swertia chirayita on MS supplemented with BAP, IAA, IBA, NAA and additives like adenine sulfate and d?glutamine with 2.5% sucrose. The best in vitro caulogenesis was observed in MS fortified with 4.43 ?M BAP in combination with IAA (0.8 ?M) that resulted increase in shoot multiplication rate. The multiplication and elongation of shoots were further enhanced by the addition of adenine sulfate (0.007%) that resulted in the further increase in multiplication fold. The addition of adenine sulfate reduced the use of other cytokinins with different auxins reported in the previous studies on Swertia chirayita. The study suggests adenine sulfate as a primary assimilable reduced nitrogen source for enhancing the shoot multiplication and elongation in Swertia chirayita. RAPD markers were employed to check the genetic variation among the clonal stock that resulted in 97% similarity. Plant Tissue Cult. & Biotech. 23(1): 11?19, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15555